International Organisations Efforts in Regulating Foreign Direct Investments in the Host States - Mohammad Belayet Hossain (Faculty of Law, Sriwijaya University, Indonesia, 2020)
Despite various efforts made by the international organisations over the decades, the idea of concluding an international agreement on foreign investment is still some way off. Due to the protest from the developing states, at this moment, international organisations do not have this item on their active agenda. The objective if this paper is to provide a thorough understanding of the law of foreign investment and the interplay between law and politics in regulating foreign investment. This paper examines two questions, namely, what are the efforts of the international organisations of regulating foreign investment? How has the law been interpreted over the years? Using doctrinal research method, this paper will critically analyse various international instruments in order to find out their effort to regulate FDI in host states. The findings of this study show that contribution made by the UN and other international organisations may not have led to a triumphant conclusion of a universal instrument but they have spelt out the main principles of law governing the treatment of foreign investment under international law.